TRPA1 está envolvido em processos oxidativos e inflamatórios induzidos por corticosterona e AOPPs em transtornos neuropsiquiátricos - Brum, Gerson Fernandes de (2024)
Neuropsychiatric disorders (NDs), such as major depressive disorder (MDD), bipolar disorder (BD) and schizophrenia (SZ), impact the lives of millions of individuals, especially those diagnosed with one of these disorders. Although the pathophysiological mechanisms involved in these NDs are distinct, there are some common characteristics: the complexity of clinical presentations, the difficulty in diagnosis and, no less important, the significant rate of refractoriness to pharmacological treatment. There are also points of agreement regarding the pathophysiological mechanisms, especially regarding the involvement of oxidative stress. Advanced oxidation protein products (AOPPs) are one of the products generated through oxidative reactions involving proteins. Few studies have investigated the relationship between AOPPs and NDs. However, the findings suggest that these markers appear to be related to worsening symptoms and reduced quality of life. Today, it is understood that AOPPs are not only markers of protein oxidative stress but also mediators of oxidative-inflammatory processes and can act on different cellular receptors, including transient receptor potentials (TRPs). Transient receptor potential ankyrin 1 (TRPA1) is a subtype of TRPs, which is an ion channel permeable to cations and activated mainly by oxidative species and inflammatory mediators. As with AOPPs, few studies have investigated the role of this receptor in neuropsychiatric disorders. Recently, specifically in an experimental model of MDD, it was demonstrated that TRPA1 antagonists reversed depressive-like behavior induced by chronic administration of corticosterone (CORT). Thus, this study aimed to (1) perform an integrative literature review on the relationship between AOPPs and TN levels and (2) investigate, in vitro, the involvement of TRPA1 in the oxidative and inflammatory processes induced by CORT and AOPPs in microglial cells (BV-2 cell line). For the literature review (Article 1), a search for studies was conducted in three databases (PubMed, Medline, and ScienceDirect), with no time limit and only in English. After applying the inclusion and exclusion criteria, 24 studies were included in the literature review. In the in vitro experimental model (manuscript 1), BV-2 cells were exposed to different concentrations of CORT and AOPPs. It was observed that higher concentrations of CORT (50 and 100 µM) reduced cell viability and increased the levels of nitric oxide (NO), reactive oxygen species (ROS), and double-stranded DNA (dsDNA). Furthermore, CORT (100 µM) increased TRPA1 and IL-17 mRNA expression. TRPA1 antagonist (HC, 1 µM) significantly prevented some of the cytotoxic effects induced by CORT. Similarly, a high concentration of AOPPs-mouse serum albumin (AOPPs-MSA) (800 µg/mL) reduced cell viability and elevated NO and dsDNA levels. However, the TRPA1 antagonist only prevented the increase in dsDNA. These findings provide new insights into the damaging mechanisms mediated by CORT and AOPPs, especially in microglial cells, making TRPA1 a potential target for novel therapeutic approaches for MDD.